Pre-surgical Language Mapping in Epilepsy: Using fMRI in Chinese-Speaking Patients - Ni, Bing; Wang, Xueyuan; Yu, Tao; Wu, Ruijie; Wang, Bo (Frontiers in Human Neuroscience, 2019)
Accurate localization of language processing areas is critical in patients undergoing epilepsy surgery. In this study, we aimed to use functional magnetic resonance imaging (fMRI), which is a non-invasive mapping method, to establish a panel of tasks investigating patients’ language function. We developed six tasks, including a series of progressive comprehension tasks from words, sentence to text, a verb generation task that can detect subtle left-brain activation, an auditory comprehension task that explored the temporal language-related areas, and a visual object naming task provided for poorly-educated patients. We successfully located the language cortex in 40 patients, and subsequently determined hemispheric dominance for the Chinese language. Our results showed a concordance between fMRI tasks and electrical cortical stimulation. The consistency across tasks, as revealed by the laterality index and concordance between the surgical outcomes, and the results of localization suggested the validity of our fMRI tasks. Our fMRI tasks also corroborate and extend the finding that the left middle frontal area (BA 9) plays an important role in reading Chinese.